A review on role of ATM gene in hereditary transfer of colorectal cancer - Sriramulu, Sushmitha; Ramachandran, Murugesan; Subramanian, Saraswathi; Kannan, Rathiusha; Gopinath, Madhumala; Sollano, Jose; Bissi, Laura; Banerjee, Antara; Marotta, Francesco; Pathak, Surajit (Acta Biomedica Atenei Parmensis, 2019)
Colorectal cancer found to be the most commonly occurring cancer worldwide which can be prevented by screening and its curable if diagnosed early. Lynch syndrome/HNPCC being an autosomal genetic disease and propensity in forming colorectal cancer is inherited wherein genomic instabilities and epigenetic changes are being the characteristic forms in hereditary cancers. It is very important to determine the polymorphism in several DNA repairing genes such as ATM, RAD51, XRCC2, XRCC3 and XRCC9 to study the risk exploring both the prognosis and the developing of colorectal cancer. The role of ATM gene has been studied which involves in the hereditary transfer of colorectal cancer associated with other related cancers such as stomach, lung and breast cancers. ATM found to be the mutation target and also a modifier gene with more risk of developing the disease by its polymorphism in variant of ATM D1853N. It was identified that ATM gene polymorphism did not drastically change HNPCC age of onset. ATM expression levels were studied and it has been concluded that the complete loss of ATM expression resulted in a propensity of worse survival and no better prognosis with increase in mortality rate. This ATM gene might be considered to be a predicted biomarker in colorectal cancer.